The Effect of Customer Relationship Marketing and Promotion on Loyalty with Customer Satisfaction as a Mediating Variable - Ilham Dwi Prabowo; Anny Nurbasari Nurbasari (PT. Global World Scientific, 2025)
This study aims to analyze the effect of Customer Relationship Marketing (CRM) and promotion on customer loyalty with customer satisfaction as a mediating variable. The research was conducted on 341 respondents of Bank Mega Buah Batu Bandung Branch customers who were selected using purposive sampling method based on certain criteria. The research data were collected through a structured questionnaire, then analyzed using the Partial Least Square (PLS) method with the help of SmartPLS 3 software. The variables studied include CRM, promotion, satisfaction, and customer loyalty as the core variables in the research model. The results showed that CRM has a significant positive effect on customer satisfaction and loyalty, both directly and indirectly through the role of satisfaction as a mediating variable. Sales promotion is also proven to have a positive effect on customer satisfaction, but its direct effect on loyalty tends to be negative. Interestingly, the effect of promotion turns positive when mediated by customer satisfaction, so the mediating role of satisfaction becomes very important. Thus, this study confirms that customer satisfaction is a crucial factor that strengthens the relationship between marketing strategies and customer loyalty. The findings provide practical implications for banks to further emphasize sustainable CRM strategies and promotions oriented towards increasing customer satisfaction in order to build long-term loyalty.